How Do Students Perceive Lecturer’s Professional Image In Digital Academic Communication? - Meylin Azizah (Universitas Islam Negeri Raden Intan Lampung, 2025)
The rapid digitalization of higher education has fundamentally transformed lecturer-student interactions, particularly accelerated by the COVID-19 pandemic. This research explores students' perspectives on the lecturer’s professional image within digital academic communication contexts. Employing a qualitative case study approach, this study involved 15 purposively selected students from the Government Science department at Universitas Muhammadiyah Lampung. Data were collected through semi-structured interviews, non-participant observations of digital interactions, and document analysis of digital communications. The study identified five primary dimensions shaping students' perceptions: (1) digital technology mastery in learning delivery, (2) communication responsiveness and timeliness, (3) ethical standards maintenance in digital interactions, (4) consistency and discipline in online instruction delivery, and (5) adaptability and innovation in digital pedagogical approaches. Findings reveal that lecturer professionalism in digital contexts extends beyond traditional academic competencies to encompass digital literacy, interpersonal communication skills, and technological adaptability. These insights underscore the necessity for comprehensive professional development programs to enhance lecturers' digital competencies aligned with evolving student expectations in the digital learning environment.